The Abbasid Historian Isaac Ibn Sulaiman Al-Hashemi (Alive 210 A.H/ 825 A.D) and his book "History and Biography" - Telfah, Modar (Dirasat: Human and Social Sciences, 2022)
This paper aims at shedding light on the Abbasid historian Isaac ibn Sulaiman Al-Hashemi (Alive 210 A.H/ 825 A.D) and his book History and Biography. Based on what other historians who copied him, the paper investigates the personal traits of Isaac ibn Sulaiman Al-Hashemi, the significance of his book, his methodology, and the fields which he was interested in incorporating in his book. The paper concludes that Isaac ibn Sulaiman Al-Hashemi adopted chronological annals methodology with special attention to accurate historiography of events including recognizing the fine details and mentioning their causes. He was also involved in covering the official positions and those who assumed them, listing the governors of the regions, exhibiting the Abbasid family disputes including the internal commotions, riots among soldiers, as well as architecture and urban planning in the city of Baghdad. The paper also reveals the significance of Isaac ibn Sulaiman Al-Hashemi and his book among historians until the mid of the 4th A.H/ 10th A.D century as he kept a record of the Abbasids' stories of the events since the start of the Abbasid era till the rule of the Caliph Al- Mamun hence assuming this prominent role among historians as a primary source for the first period of Abbasid history.